The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1080/23311916.2020.1723211
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of occupational accident; and injuries and their associated factors in iron, steel and metal manufacturing industries in Addis Ababa

Abstract: The purpose of the research is to investigate the prevalence of workplace accident/injuries (policymakers) and the associated factor in Iron, Steel and Metal Manufacturing Industries (ISMMI) in Addis Ababa, Ethiopia. To achieve this objective, primary data using a questionnaire was collected from 446 production workers in 89 ISMMI. The major findings of the study showed that both availability and cultures of Personal Protective Equipment (PPE) usage are found to be lower. The prevalence of workplace AoI in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 34 publications
1
13
0
3
Order By: Relevance
“…We found that the risk of injury was higher in factories with more than three workers, suggesting that it might be difficult to maintain occupational safety in large factories as there is a lack of proper safety practices and monitoring by the local authority. A similar finding is reported from iron, steel and metal manufacturing industries in Ethiopia where occupational injuries were more common in medium or large size industries than the small size industries [22].…”
Section: High Annual Rate Of Injuries and Their Causes And Consequencessupporting
confidence: 83%
“…We found that the risk of injury was higher in factories with more than three workers, suggesting that it might be difficult to maintain occupational safety in large factories as there is a lack of proper safety practices and monitoring by the local authority. A similar finding is reported from iron, steel and metal manufacturing industries in Ethiopia where occupational injuries were more common in medium or large size industries than the small size industries [22].…”
Section: High Annual Rate Of Injuries and Their Causes And Consequencessupporting
confidence: 83%
“…Günümüzde teknolojideki hızlı gelişmeler ve pazardaki üretim ve rekabetteki hızlı artış, iş sağlığı ve güvenliğine yönelik tehditleri daha da artırmıştır (Akay vd., 2021). İş kazası / yaralanma /can kaybına, çalışanların verimliliğinin azalmasına önemli ölçüde katkıda bulunduğundan ve daha sonra ekonomiyi büyük ölçüde etkilediğinden, iş güvenliği, küresel endüstrilerin en yüksek önceliği haline gelmiştir (Berhan, 2020). İş kazası, özellikle bireylerin yaşamları üzerinde ciddi olumsuz ekonomik ve sosyal etkileri olan, çalışanların verimliliğinin azalmasına önemli ölçüde neden olan, sanayileşmiş kesimlerde her çalışmanın ayrılmaz bir parçasıdır ve iş sonucunda veya iş sırasında meydana gelen ve ölümcül / ölümcül olmayan mesleki yaralanmalara yol açan bir olaydır.…”
Section: Genel Hatlarıyla İş Kazasıunclassified
“…To improve workplace safety and reduce accident rates, these issues must be considered for the sake of improving companies' operations [16]. According to Berhan [7], there are about 268 million work-related diseases and non-fatal workplace accidents worldwide every year. It is an important task to actively examine and evaluate workers' workplace safety issues, otherwise, work efficiency and the social economy will be affected.…”
Section: Review Of Manufacturing Risk Assessmentmentioning
confidence: 99%